Our Future Mind: Epochal Developments of Perinatal Clinical Psychology - Imbasciati, Antonio (International Journal of Child Health and Nutrition, 2014)
This paper clarifies the meaning of Perinatal Clinical Psychology by removing the prejudice and the stereotypes that unfortunately pervade children health care facilities still nowadays. The author goes over the basic principles that neuroscience has recently demonstrated in the development of the brain from the fetus to the infant, the child and the adult. The brain is self-generating through experience and not on the basis of genome. Epygenetics accounts for it. The brain needs to learn so as to be able to develop. Nobody has a brain that is the same as anybody else’s and therefore nobody has a mind that is the same as anybody else’s. The brain generates the mind and, in turn, the mind regenerates the brain in a ceaseless feedback. The experience that generates and renews the brain continuously comes from interpersonal relationships. The greatest incidence of this kind of development comes from the relationships with the parents and the caregivers and depends on the emotional moment of the relationship. This opens up transgenerational perspectives. The quality of the mind (and the brain) of the parents and caregivers produces the quality of the mind of the children. The latter, in turn, become adults, condition the mind of their children in cascade effect from one generation to the following. This transmission can produce an improvement but also a worsening for the future generations. As a consequence, Perinatal Clinical Psychology becomes important for prevention and psychological support to the children and the families at risk.